International workshop “The Varieties of Power in the Economy”, NRU HSE, Moscow, July 3–4, 2020 - Board, Editorial (Journal of Economic Sociology, 2020)
Journal of Economic Sociology. Vol. 21. No 1. January 2020www.ecsoc.hse.ru140International workshopThe Varieties of Power in the Economy3–4 July 2020Laboratory for Studies in Economic Sociology, National Research University “Higher School of Economics” (NRU HSE), Moscow, Russia Deadline for Submissions—15 February 2020